Muslim consumers' perceived behavior in E-commerce environment - Suhaimi, Mohd Adam; Mohamed Razi, Mohamed Jalaldeen; Hussin, Husnayati; Muhammad, Muhd. Rosydi; Muhammad, Marjan (IEEE Computer Society, 2013)
Muslim consumers are believed to be more concerned whether the current e-commerce processes are mixed with un-Islamic elements such as, riba (interest), gharar (uncertainty), and Maisir (gambling). To clarify the misconception, it is suggested that an assurance be given by a reputable Islamic religious authority to the effect that Internet seller complies with an Islamic law (Shariah) -compliant e-commerce model. The present work empirically investigates the Muslim consumers’ perceived behavior in e-commerce environment by collecting data from 162 staff from International Islamic University Malaysia (IIUM). However, the findings suggest that third party assurance from an Islamic authority does not much influence on consumers’ perceived behavior in e-commerce environment.